2015
DOI: 10.1002/ajpa.22819
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal manifestation of malaria: An epidemiological approach using documented skeletal collections

Abstract: Several etiological explanations for the characteristic malarial skeletal lesions are explored, including severe malarial anemia, an imbalance in bone remodeling, and extramedullary erythropoiesis. The importance of careful differential diagnoses between other infectious and noninfectious causes of these lesions is discussed, including the potential for coinfection of malaria with other infectious diseases. The findings of this study are pivotal in establishing diagnostic criteria by which we can identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 52 publications
0
38
1
Order By: Relevance
“…Apart from all these conditions, at that time, malaria was a disease present both in Africa and Portugal (Morais, ). Recent studies suggested that such disease may be in the origin of several skeletal lesions, namely, a combination of cribra orbitalia, cribra humeralis, cribra femoralis, and porotic hyperostosis (Smith‐Guzman, ), which is precisely the type of lesions recorded. Therefore, it should not be excluded the hypothesis of some of these lesions had been caused by malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from all these conditions, at that time, malaria was a disease present both in Africa and Portugal (Morais, ). Recent studies suggested that such disease may be in the origin of several skeletal lesions, namely, a combination of cribra orbitalia, cribra humeralis, cribra femoralis, and porotic hyperostosis (Smith‐Guzman, ), which is precisely the type of lesions recorded. Therefore, it should not be excluded the hypothesis of some of these lesions had been caused by malaria.…”
Section: Discussionmentioning
confidence: 99%
“…). The protozoal parasite that causes malaria leaves telltale signs on the skeletal remains of humans, suggesting that disease pathology might be a useful indicator of infection for some parasites (Smith‐Guzmán ). The plausible span for study of parasites in fossilized remains stretches back to the Devonian, approximately 400 million years BP.…”
Section: Archaeo‐ and Paleoparasitologymentioning
confidence: 99%
“…The specific archaeological sites were: 1) Pre-Nuragic-Ossi, "S'adde 'e Asile", [33] and other localities [24] [34]- [39]. Paleopathologists of the Mediterranean basin consider skeletal remains with PH to be a sign of chronic hemolytic anemia caused by malaria, thalassemia, and sickle cell disease.…”
Section: Methodsmentioning
confidence: 99%